A systematic review of effective therapeutic interventions and management strategies for challenging behaviour in women in forensic mental health settings. Issue 4 (4th July 2019) - Tolland, Heather; McKee, Tracey; Cosgrove, Sarah; Drysdale, Emma; Gillespie, Mark; Paterson, Lesley; Totten, Catherine
ABSTRACT: Women in secure forensic mental health care require therapy and care that is responsive to their specific needs. Despite the policy recognition that women require a distinct service, evidence based practice is not available for this population. This review was undertaken in response to a clinical need within a medium secure unit in Glasgow that was experiencing high levels of challenging behaviour, in a female ward. The review aimed to identify effective strategies or interventions for the management of challenging behaviour in women in secure services and, therefore, improve practice and patient care. A synthesis of the findings from the 11 identified studies revealed variability in the approaches used to support women in forensic services, including: behavioural programmes; organisational change with a focus on staff training and support; medication; ECT and mechanical restraint. The challenging behaviours assessed included self-harm; physical and verbal aggression; suicide attempts and arson/fire setting. The majority of articles suggested some improvement in aspects of challenging behaviour, however this was limited by the lack of control groups and small sample sizes. Further investigation is required to find out whether interventions identified in this review can sustain a reduction in challenging behaviours in the long-term.